External Genital warts in HIV-infected patients with sexually transmitted infections in Ibadan, Nigeria (2017)
Background: Human Papilloma Virus (HPV) infection in the genital area is usually asymptomatic, and when symptomatic, manifests in either benign or malignant forms. This study aims at providing information on the prevalence of external genital warts (EGWs) among people living with HIV (PLWHIVS) attending Antiretroviral Treatment (ART) clinic at the University College Hospital, Ibadan, Nigeria. Methods: This is a descriptive cross-sectional survey of PLWHIVS attending ART clinic between January 2006 and December 2007. Diagnosis of genital warts was based on the findings of typical lesions on the external genitalia, vaginal, cervix or perianal region after clinical examination and informed consent from cach participant. Antibodies against Herpes and HPV were measured using, Enzyme-linked immunosorbent Assay (ELISA). Results: A total of 5,207 patients, 3519 female and 1688 males attended the ART clinic during the period. The mean age of the patients was 34.67 yrs (9.16). Five hundred and forty-two (10.0%) had various sexually transmitted infections (STIs). The prevalence of anogenital warts was 3.65% among the HIV-infected patients and 35.0 % among the subset of HIV-infected patients with STIs. The prevalence of genital warts was 1.5 times higher in treatment experienced patients (OR=1.46; 95%CI: 1.02, 2.10). Genital wart was found to be associated with low CD4 count, high viral load, treatment- experience and non-use of condom during sexual intercourse. (P=0.002). Conclusions: External genital warts are common among people living with HIV infection. According to the appropriate guidelines, HPV vaccine should also be offered to HIV-infected adolescents that are non-reactive to the virus.